The relationship between social support and physiological processes A review with emphasis on underlying mechanisms and implications for health. [article]. - Uchino, Bert N.
In this review, the authors examine the evidence linking social support to physiological processes and characterize the potential mechanisms responsible for these covariations. A review of 81 studies revealed that social support was reliably related to beneficial effects on aspects of the cardiovascular, endocrine, and immune systems. An analysis of potential mechanisms underlying these associations revealed that (a) potential health-related behaviors do not appear to be responsible for these associations; (b) stress-buffering effects operate in some studies; (c) familial sources of support may be important; and (d ) emotional support appears to be at least I important dimension of social support. Recommendations and directions for future research include the importance of conceptualizing social support as a multidimensional construct, examination of potential mechanisms across levels of analyses, and attention to the physiological process of interest.-- (from the author)